OPT Policy Changes and Foreign Born STEM Talent in the U.S. - Amuedo-Dorantes Catalina; Delia Furtado; Huanan Xu (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2019)
Academia and the public media have emphasized the link between STEM majors and innovation as well as the need for STEM graduates in the U.S. economy. Given the proclivity of international students to major in STEM fields, immigration policy may be used to attract and retain high-skilled STEM workers in the United States. We examine the impacts of a 2008 policy extending the Optional Practical Training (OPT) period for STEM graduates. Using data from the National Survey of College Graduates, we find that, relative to other foreign-born U.S. college graduates, the foreign-born who first came on student visas were 18 percent more likely to have their degrees in STEM fields if they enrolled in their major after the OPT policy change. While part of this increase is likely due to the rather mechanical drop in return migration among STEM graduates following the OPT change, the policy also appears to have induced some international students, who may have otherwise chosen a different field, to major in STEM.
Keywords: F22; J61; J68; 330; Optional Practical Training; H-1B visas; foreign-born workers; United States